2021
DOI: 10.3390/catal11080967
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of Extended Ripening Effects on Peptides Evolution and DPPH Radical Scavenging Activity in Mexican Goat Cheese

Abstract: Cheese ripening causes intense proteolysis, particularly when the cheese contains starter cultures. Several studies have shown the presence of bioactive peptides in goat’s milk cheeses with antioxidant activity. Mexican goat cheeses’ peptide fractions were evaluated at different ripening stages. Additionally, they were correlated with their antioxidant activity. Proteolysis was measured in the acid-soluble nitrogen and non-protein nitrogen fractions using reverse-phase high-performance liquid chromatography. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In another study, Vázquez-Garcí et al . (2021) also related DPPH radical scavenging activity of Mexican goat cheese to the peptides originally present in goat's milk. Hence, it may be assumed that the antioxidant potential of goat's milk paneer prepared in the present study might be due to presence of different proteins, their peptides and free amino acids, as well as the contribution from the citrus juices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Vázquez-Garcí et al . (2021) also related DPPH radical scavenging activity of Mexican goat cheese to the peptides originally present in goat's milk. Hence, it may be assumed that the antioxidant potential of goat's milk paneer prepared in the present study might be due to presence of different proteins, their peptides and free amino acids, as well as the contribution from the citrus juices.…”
Section: Discussionmentioning
confidence: 99%
“…Goat's milk can be converted into many products, such as cheese, yogurt, milk powder, ice-cream, butter and fermented milk products (Ribeiro and Ribeiro, 2010; Nayik et al ., 2021) and could potentially have use in the production of infant formula (Prosser, 2020; Vázquez-García et al . (2021) analyzed antioxidant peptides in Mexican goat cheese fractions (acid-soluble and non-protein nitrogen) during ripening. They suggested that the ripened Mexican goat cheese showed DPPH radical scavenging activity owing to the presence of peptides which were either present originally in the milk or released by the actions of starter culture during ripening.…”
mentioning
confidence: 99%
“…The ricotta cheese, which was enriched with a fortification level of 5%, demonstrated a concentration of approximately 30 mg of bioactive peptides. The investigation conducted by Vázquez-García et al involved the assessment of peptide fractions found in Mexican goat cheeses during different ripening periods [13]. An examination was conducted to explore the correlation between the peptide fractions and the antioxidative properties demonstrated by the cheeses [13].…”
Section: Cheese Type Bioactive Peptides Bioactivities Referencesmentioning
confidence: 99%
“…The investigation conducted on Gouda cheese demonstrated that utilizing proteases derived from Lactobacillus helveticus led to the production of peptides exhibiting antihypertensive properties [12]. In addition, a study on blue cheese showed that the ripening process led to the formation of peptides with antioxidant activity [13]. Furthermore, a study on Camembert cheese showed that the ripening process led to the formation of peptides with antithrombotic activity [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation